Carlactone-type strigolactones and their synthetic analogues as inducers of hyphal branching in arbuscular mycorrhizal fungi. (October 2016) - Mori, Narumi; Nishiuma, Kenta; Sugiyama, Takuya; Hayashi, Hideo; Akiyama, Kohki
Abstract: Hyphal branching in the vicinity of host roots is a host recognition response of arbuscular mycorrhizal fungi. This morphological event is elicited by strigolactones. Strigolactones are carotenoid-derived terpenoids that are synthesized from carlactone and its oxidized derivatives. To test the possibility that carlactone and its oxidized derivatives might act as host-derived precolonization signals in arbuscular mycorrhizal symbiosis, carlactone, carlactonoic acid, and methyl carlactonoate as well as monohydroxycarlactones, 4-, 18-, and 19-hydroxycarlactones, were synthesized chemically and evaluated for hyphal branching-inducing activity in germinating spores of the arbuscular mycorrhizal fungus Gigaspora margarita . Hyphal branching activity was found to correlate with the degree of oxidation at C-19 methyl. Carlactone was only weakly active (100 ng/disc), whereas carlactonoic acid showed comparable activity to the natural canonical strigolactones such as strigol and sorgomol (100 pg/disc). Hydroxylation at either C-4 or C-18 did not significantly affect the activity. A series of carlactone analogues, named AD ester and AA'D diester, was synthesized by reacting formyl Meldrum's acid with benzyl, cyclohexylmethyl, and cyclogeranyl alcohols (the A-ring part), followed by coupling of the potassium enolates of the resulting formylacetic esters with the D-ring butenolide. AD ester analogues exhibited moderate activity (1 ng–100 pg/disc), while AA'D diester analogues having cyclohexylmethyl and cyclogeranyl groups were highly active on the AM fungus (10 pg/disc). These results indicate that the oxidation of methyl to carboxyl at C-19 in carlactone is a prerequisite but BC-ring formation is not essential to show hyphal branching activity comparable to that of canonical strigolactones. Graphical abstract: Carlactone-type strigolactones and their synthetic analogues were shown to induce hyphal branching in AM fungi. Highlights: Carlactone-type strigolactones and carlactone analogues were synthesized. Hyphal branching-inducing activity in Gigaspora margarita was evaluated. Carlactonoic acid showed comparable activity to canonical strigolactones. Synthetic carlactone analogues lacking the BC-rings also showed the activity. Carlactone-type strigolactones can act as symbiotic signals for AM fungi.